Anti-Arthritic Activity of Bartogenic Acid Isolated from Fruits of Barringtonia racemosa Roxb. (Lecythidaceae) - Patil, Kalpesh Ramdas (Hindawi Publishing Corporation, 2011)
The fruits of Barringtonia racemosa are prescribed in the ayurvedic literature for the treatment of pain, inflammation and rheumatic conditions. In present investigation, activity guided isolation of bartogenic acid (BA) and its evaluation in the Complete Freund's Adjuvant (CFA)-induced arthritis in rats is reported. Among the various extracts and fractions investigated preliminarily for carrageenan-induced acute inflammation in rats, the ethyl acetate fraction displayed potent anti-inflammatory activity. Large-scale isolation and characterization using chromatography and spectral study confirmed that the constituent responsible for the observed pharmacological effects was BA. Subsequently the BA was evaluated for effectiveness against CFA-induced arthritis in rats. The results indicate that at doses of 2, 5, and 10 mg kg(−1) day(−1), p.o., BA protects rats against the primary and secondary arthritic lesions, body weight changes and haematological perturbations induced by CFA. The serum markers of inflammation and arthritis, such as C-reactive protein and rheumatoid factor, were also reduced in the BA-treated arthritic rats. The overall severity of arthritis as determined by radiological analysis and pain scores indicated that BA exerts a potent protective effect against adjuvant-induced arthritis in rats. In conclusion, the present study validates the ethnomedicinal use of fruits of B. racemosa in the treatment of pain and inflammatory conditions. It further establishes the potent anti-arthritic effects of BA. However, additional clinical investigations are needed to prove the efficacy of BA in the treatment of various immuno-inflammatory disorders.